2016
DOI: 10.1177/0003702816631313
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Carbon Steel with Multi-Line Internal Standard Calibration Method Using Laser-Induced Breakdown Spectroscopy

Abstract: A multi-line internal standard calibration method is proposed for the quantitative analysis of carbon steel using laser-induced breakdown spectroscopy (LIBS). A procedure based on the method was adopted to select the best calibration curves and the corresponding emission lines pairs automatically. Laser-induced breakdown spectroscopy experiments with carbon steel samples were performed, and C, Cr, and Mn were analyzed via the proposed method. Calibration curves of these elements were constructed via a traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In recent years, many studies have detailed the use of LIBS for elemental depth profiling and mapping. 2–28 The reader is pointed toward a recent review by Jolivet et al for more thorough exposition of published LIBS imaging studies. 22 The LIBS technique involves irradiation of a sample with an intense, focused beam of light from a pulsed laser source.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have detailed the use of LIBS for elemental depth profiling and mapping. 2–28 The reader is pointed toward a recent review by Jolivet et al for more thorough exposition of published LIBS imaging studies. 22 The LIBS technique involves irradiation of a sample with an intense, focused beam of light from a pulsed laser source.…”
Section: Introductionmentioning
confidence: 99%
“…LIBS offers distinct advantages for in situ, real-time, standoff, and contactless detection, and it requires less sample preparation and consumption [2]. This technique is widely applied to the fields of energetic materials [3], metallurgical engineering [4], space exploration [2], industry manufacture [5], food safety [6], environmental monitoring [7], agricultural product [1], resources and energy [8], archaeology [9], and clinical diagnostics [10]. However, the stability and repeatability of the plasma emission, along with the detection accuracy, are easily altered by the wavelength of the input light, pulse duration and its energy, the distance of lens-to-sample, and the target characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [25], we demonstrated that an internal standard method [26,27] is necessary to have a better result for quantitative analysis. The upper transition energy levels for these two lines are close to 7.685 eV for C I and 8.038 eV for the Fe II line (204.06 nm).…”
Section: Resultsmentioning
confidence: 96%